(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Contributo non sottoposto a valutazione.Il saggio, con l’originario titolo integrale Per una equa mondializzazione delle periferie nelle società plurali. La lunga (ma, forse, istruttiva) storia dell’attivazione di un ‘nuovo’ Corso di laurea sull’interculturalità, è destinato agli Studi in onore del Prof. Mario Tedeschi, ed è altresì inserito fra i contributi ai lavori della Prima Sessione del Convegno Diritto e religioni. Declinazioni della giuridicità nel contesto di una società multiculturale e multireligiosa, organizzato in data 1-2 dicembre 2016 dalla Prof.ssa Beatrice Serra presso l’Università degli Studi di Roma La Sapienza SOMMARIO: 1. Il vortice iperbolico del bacino euromediterraneo e il ‘bergamotto dell’interculturalità’ - 2. Il ‘made in Italy’ dantesco e il doppio registro delle Università per stranieri nel “bel paese là dove ‘l sì suona“ - 3. Il ‘bisogno di mondo’ e la rifrazione in alto dell’identità plurale della Calabria - 4. L’imperativo del ‘Mare Amoroso’ e gli ‘ottativi categorici’ mirati a una sostanziale e concreta giustizia - 5. Dante prima e oltre Kant: dalla ‘giustizia della carità’ alla ‘carità della giustizia’ - 6. Ancora: di un’inedita sperimentazione accademica e civile. ABSTRACT: For a fair globalization of the suburbs in plural societies: a ’new’ Bachelor’s Degree in Interculturality. With this essay the author, actually Rector of the University for Foreigners "Dante Alighieri" of Reggio Calabria, is to illustrate the steps that have led to the activation of a Bachelor’s Degree (in some respects) innovative, induced by contemporary issues of migration flows and by the dynamics of international mobility, become remarkably more rapid and pressing in conjunction with the related phenomena of globalization. They impose, even to the higher education institutes, a timely and in-depth rethinking and an accurate taking of responsibility, with the respect to their relevant areas of teaching and training program. The trial that is intended to give through the above-mentioned Degree was modeled on the basis of some previous initiatives, taken by the University for Foreigners of Reggio Calabria, even if the model now proposed benefits from the innovative results induced by synergies with other Universities for Foreigners, in particular that of Siena, as well as the consultation put in place with the Ministry of Education, the Interior Ministry and the EU, and the cooperation with civil society organizations, primarily the Community of Sant’Egidio.